Identifying Local Health Issues Using Data Analytics and Data Mining Method from a Large-Combined Datasets of Supermarket and Health Centre - Masoud Mohammadian (Prosiding International conference on Information Technology and Business (ICITB), 2020)
A large amount of the data was stored from people’s activities in buying products. The real-time analysis method was able to be used to provide information about health and wellbeing of people who particularly lived in a countries, cities, or suburb area of the world. This health and wellbeing information was submitted to the decision makers (e.g., policy makers, government officials, and health professionals) to change policies, created innovative solution, and improved the daily life of people. With current power of the data mining and the data analytic methods, it was currently possible to collect the data about human activities (e.g., the data of buying smartwatches, smartphones, and health consultation) so that the human activities and wellbeing of people were identified. This data analysis was able to improve the understandings of physical and mental wellbeing of people; to detect the unknown health issues and behaviours; and, to provide the solutions to support people. The result of this data analysis was able to provide the solutions for all purposes (e.g., current health programs, health policies in terms of sugar and oil selling in supermarket, and bicycle, footpaths, parks and recreational place designs), to improve better health facilities for neighbourhoods and cities, and to allocate funds to combat obesity. The available data about the supermarket product purchases, physical activities, health problems, and social interactions and communication provided the information of the profile of health people. The data of supermarket purchases, smartwatch purchases, and smartphone purchases were able to provide the information about the life and activities of people. The formulations of the problems were: how were the collected data able to be utilized to improve the life of people? Was it sufficient to analyse the data of food buying and online activities of people to make the decision making and improve the life of people? Were the collected data of the supermarket and online activities sufficient to be used for determining the profile of health people? Were the collected data from supermarket product purchases, smartwatches, and smartphones with or against you? This discussion gave the understandings of the data mining in identifying the health problems based on the collected data of human activities and product purchases.Keywords:       Data Analytics, Data Mining, Supermarket, Health Data